DEVELOPMENT OF A METHODOLOGY FOR EVALUATING QUALITY COST IN A SEMIMECANIZED LOGGING OPERATION - Jacovine, Laércio Antônio Gonçalves (1999)
The etudy made a description and use of a methodology for evaluating quality cost in a semimechanized    logging   operation   was   developed. For  description  this  goal the logging sub-operations were detailed. The effects of the non conformity of one sub-operation on the succeeding ones were listed and analysed. Those consequences on which a money value could be atributed were specified. The methodology was applied to a case study. Quality cost were divided in three categories: evaluation cost, prevention cost, and faillure cost. It was concluded that the firm is not investing enough in evaluation and prevention causing a faillure cost of R$1.541,11/ha, which is considered too high. The percent composition of this cost was: log spliting 40,96%; error in wood volume determination in the stocking yeard 37,12%; wood waste in the stand 9,52%; non separation of thin logs 8,46%; logs left in the fire control line 1,49%; miscalculation of splited wood volume 1,53%; wood volume remaining in the coppices 0,51%; presence of branches in the fire control line 0,41%. The logs spliting operation must be worked out in order to diminish its cost. Firm profit may be increased throught investiment and research in reducing evaluation and prevention costs. Every waste cost must be avoided because is not only the firm itself, but the whole society who ends up paying the bill.